2014
DOI: 10.1111/ruso.12040
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the Multiple and Shifting Identities of Farm Women in the Northeastern United States

Abstract: The identities of women on farms are shifting as more women enter farming and identify as farmers, as reflected by the 30 percent growth in women farmers in the U.S. census of agriculture (USDA 2009). This article draws from identity theory to develop a quantitative measure of the identities of farm women. The measure incorporates multiple roles farming women may perform and weights these roles by their salience to two farm identities, farm operator and farm partner. We use a sample of women on farms (n = 810)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 22 publications
(43 reference statements)
4
45
0
Order By: Relevance
“…Trauger () argues that women are transgressing traditional gender roles by claiming the identity of “farmer,” and are more comfortable doing this in sustainable than industrial agricultural spaces. Women are more likely to report being the principal operators on U.S.‐certified organic farms (22 percent) than farms in general (12 percent), but these statistics likely underreport the actual number of women farming (Brasier et al ; Sachs et al ; U.S. Department of Agriculture ). Although the title “farmer” is typically associated with heterosexual men (Campbell, Bell, and Finney 2006), women play critical roles in food systems (Allen and Sachs ), and are increasingly identifying as farmers (Brasier et al ; Sachs et al ).…”
Section: Literature Review: Gender and Sexuality In Sustainable Agricmentioning
confidence: 99%
See 1 more Smart Citation
“…Trauger () argues that women are transgressing traditional gender roles by claiming the identity of “farmer,” and are more comfortable doing this in sustainable than industrial agricultural spaces. Women are more likely to report being the principal operators on U.S.‐certified organic farms (22 percent) than farms in general (12 percent), but these statistics likely underreport the actual number of women farming (Brasier et al ; Sachs et al ; U.S. Department of Agriculture ). Although the title “farmer” is typically associated with heterosexual men (Campbell, Bell, and Finney 2006), women play critical roles in food systems (Allen and Sachs ), and are increasingly identifying as farmers (Brasier et al ; Sachs et al ).…”
Section: Literature Review: Gender and Sexuality In Sustainable Agricmentioning
confidence: 99%
“…Women are more likely to report being the principal operators on U.S.‐certified organic farms (22 percent) than farms in general (12 percent), but these statistics likely underreport the actual number of women farming (Brasier et al ; Sachs et al ; U.S. Department of Agriculture ). Although the title “farmer” is typically associated with heterosexual men (Campbell, Bell, and Finney 2006), women play critical roles in food systems (Allen and Sachs ), and are increasingly identifying as farmers (Brasier et al ; Sachs et al ). Women may be attracted to sustainable farming for the feelings of independence and autonomy it affords, the opportunity to do traditionally masculine tasks, and “a work culture that does not emphasize mechanization or synthetic chemical use” (Trauger :304).…”
Section: Literature Review: Gender and Sexuality In Sustainable Agricmentioning
confidence: 99%
“…Research by Brasier et al () suggests that life transitions are important to understanding women's farmland management, and census data of Iowa landowners suggests the same (Duffy and Johanns ). These studies are consistent with research that has identified widowhood as a time of life in which women have more or the most power in regard to their farms because they are no longer dependent on male partners for decision making (Brasier et al ; Pilgeram and Amos ; Sachs ; Salamon and Keim ). As women farmland owners outlive their spouses, co‐owners become sole owners and may have opportunities to implement changes to their farmland that were previously complicated by the wishes of co‐owners.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…While institutional attention to the importance of women in agriculture is increasing (see Harden ), agricultural systems remain gendered in ways that privilege the power of men (Sachs ; Trauger et al ; Wells and Eells ). Recent research emphasizes the importance of social relationships in shaping who controls the land, its use, and its future (Brasier et al ; Druschke and Secchi ; McMillan Lequieu ). Previous studies have found that tenants, rather than landowners, make land management decisions and that gender plays a significant role in landowners’ involvement in the management of their land (Petrzelka and Marquart‐Pyatt ; Wells and Eells ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation